EU Chemical Plant Protection Products in 2023: Current State and Perspectives - Patrice A. Marchand (Agrochemicals, 2023)
Agrochemicals are synthetic or hemi-synthetic crop protection substances which are supervised by the EU Regulation EC 1107/2009, which give rise to plant protection products (PPP) with market authorizations. Most of these active substances of chemical origin were transferred from the previous Annex I of Directive 91/414/EEC to Part A of Regulation EU 540/2011, with newly approved active substances mainly being listed in Part B or E, while renewed substances were moved from Part A to Part B or E. In this study, approved agrochemicals from the early part of 2023 are organized into categories, families, functions, usages, treated crop categories, regulatory characteristics, and maximum residue limits (MRLs). Perspectives regarding their evolution are also described together with pending approvals.